A Recombinant Subunit Based Zika Virus Vaccine Is Efficacious in Non-human Primates - Medina, Liana O.; To, Albert; Lieberman, Michael M.; Wong, Teri Ann S.; Namekar, Madhuri; Nakano, Eileen; Andersen, Hanne; Yalley-Ogunro, Jake; Greenhouse, Jack; Higgs, Stephen; Huang, Yan-Jang S.; Vanlandingham, Dana L.; et al. (Frontiers in Immunology, 2018)
Zika Virus (ZIKV), a virus with no severe clinical symptoms or sequelae previously associated with human infection, became a public health threat following an epidemic in French Polynesia 2013-2014 that resulted in neurological complications associated with infection. Although no treatment currently exists, several vaccines using different platforms are in clinical development. These include nucleic acid vaccines based on the prM-E protein from the virus and purified formalin-inactivated ZIKV vaccines (ZPIV) which are in Phase 1/II clinical trials. Using a recombinant subunit platform consisting of antigens produced in Drosophila melanogaster S2 cells, we have previously shown seroconversion and protection against viremia in an immunocompetent mouse model. Here we demonstrate the efficacy of our recombinant subunits in a nonhuman primate (NHP) viremia model. High neutralizing antibody titers were seen in all protected macaques and passive transfer demonstrated that plasma from these NHPs was sufficient to protect against viremia in mice subsequently infected with ZIKV. Taken together our data demonstrate the immunogenicity and protective efficacy of the recombinant subunit vaccine candidate in NHPs as well as highlight the importance of neutralizing antibodies in protection against ZIKV infection and their potential implication as a correlate of protection.